Method for testing anti-poison performance of barrier material
By simplifying the testing method for protective performance against poison gas, the complexity and danger of mustard gas testing have been solved, enabling safe and efficient material performance evaluation and reducing the risk of injury to test personnel and material waste.
Patent Information
- Application Number
- CN202411634658.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-11
AI Technical Summary
In existing technologies, the mustard gas test method is complex and dangerous, resulting in a high risk of injury to test personnel, and making it difficult for companies to accurately assess the performance of protective materials.
A new method for testing the protective performance of barrier materials against toxic substances is adopted. This method simplifies the testing of protective performance and calculates the protection time by steps such as weighing, swelling, calculating the molar amount of absorbed solvent, plotting curves, and calculating the diffusion coefficient.
It simplifies the testing of anti-toxic performance, protects the safety of test personnel, improves the accuracy of material performance evaluation, and reduces material waste and the use of mustard gas.
Smart Images

Figure CN119595488A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material evaluation, in particular to the field of material anti-toxic performance testing, and specifically to a method for testing the anti-toxic performance of a barrier material. Background Art
[0002] At present, mustard gas is mainly used for the performance test of chemical agents for protective equipment such as gas masks, gas suits and gas gloves. According to GB2394-95 "Test method for the performance of breathable anti-toxic clothing - Determination of the "gas-to-gas" anti-toxic time of mustard gas", under the specified test conditions, the contaminated air containing a certain concentration of mustard gas is continuously passed through the breathable anti-toxic clothing material to be tested, and the mustard gas vapor that passes through the material is absorbed by methyl isobutyl methanol absorption liquid, and the mustard gas content in the absorption liquid is determined by DB-3 colorimetry, so as to determine the "gas-to-gas" anti-toxic time when the cumulative dose of mustard gas vapor that passes through the material reaches the allowable dose.
[0003] However, mustard gas is a powerful blistering agent that is colorless and odorless. When the human body is exposed to the "liquid-gas" of mustard gas, there is little or no pain. Within 24 hours after exposure, these substances will form small and large blisters on the skin, which always have an irritating effect and can easily cause casualties during the test.
[0004] The mustard gas "liquid-gas" protection time test method in GJB 6629-2008 "Military Isolation Personal Protective Equipment Specification" is to add a certain amount of mustard gas liquid drops on the tested material under the specified test conditions. Mustard gas begins to penetrate into the material. When vapor mustard gas escapes from the other side of the material and contacts the Congo red-chloramine standard indicator paper, mustard gas reacts with chloramine to generate hydrochloric acid, which then reacts with Congo red to change the Congo red-chloramine standard indicator paper from red to blue, indicating the end point of the reaction. This period of time is called the "liquid-gas" protection time of the material against mustard gas. The test method requires placing the sample in a No. 6 instrument, sequentially adding poison to the sample in the No. 6 instrument, and keeping the liquid poison on the sample at all times. The test instrument is complex and the test steps are complex. At the same time, since most companies do not have the test conditions, it is impossible to judge the protective performance of the materials used during the research and development process, which is not conducive to the optimization and improvement of product performance and the protection of test personnel, and it is very easy to cause injury to test personnel. Summary of the invention
[0005] The present invention provides a method for testing the anti-toxic performance of barrier materials in order to solve a series of problems such as the current human body is not easily detected in the short term when exposed to mustard gas "liquid-gas", but has a stimulating effect, and most companies are unable to judge the performance of protective materials during the research and development process, which is not conducive to the protection of test personnel.
[0006] The present invention is implemented by the following technologies: The present invention provides a method for testing the anti-toxic performance of a barrier material, comprising the following steps: a. Sample weighing Take any one of plastic, rubber-plastic blend, and rubber-combined material as the sample to be tested, take a sample with uniform thickness from the sample to be tested, weigh and record the mass M1 of the sample, and the weighing result should be accurate to 1 mg.
[0007] b. Swelling The sample piece is naturally placed in 50mL of 2-CEES solvent contained in a brown wide-mouthed frosted glass bottle with a stopper. The sample piece is shaken to completely immerse in the solvent. After the sample piece is immersed, the bottle stopper is tightly closed and sealed. The sealed bottle is stored at 36℃±1℃ in a constant temperature box. The stability is referenced to the mustard gas "liquid-gas" protection time test method in GJB 6629-2008. Sampling is performed at intervals until the sample piece has swelled to equilibrium. Specifically, sampling is performed at 0.5h, 1h, 2h, 4h, 6h, 8h, 10h, and 24h, respectively, to allow it to fully reach swelling equilibrium.
[0008] c. Sampling and processing After gently wiping off the solvent adhering to the surface of the sample, weigh the mass of the sample (M2-M0) to an accuracy of 1 mg; Specifically, the following steps are included: use tweezers to pick up a sample from a brown wide-mouthed frosted glass bottle with a stopper and place it on a clean and dry filter paper; quickly close the filter paper and wipe off the solvent on the surface of the sample; then use tweezers to pick up the sample and transfer it to a weighing bottle with a mass of M0 that has been constant weight; immediately cover the weighing bottle cap and weigh it within 30 seconds. The total mass of the weighing bottle and the sample is recorded as M2, accurate to 1 mg; after weighing, shake off or blow off the remaining organic solvent in the weighing bottle before weighing the next sample.
[0009] d, calculation of molar amount of absorption solvent Molar amount of solvent absorbed by the sample Q t Determine it through the following formula ① Qt= ×100% ① Where: Qt – the molar amount of solvent absorbed by the sample at a specific time t; (M2- M0) - M1 – the mass of solvent absorbed by the sample; M1——Quality of the sample.
[0010] e, draw the curve to calculate the diffusion coefficient According to step d, the molar amount of solvent absorbed by the sample at different times is plotted. The curve is obtained and the fitting equation ② is obtained, wherein the dynamic swelling data can be used to analyze the mechanism of penetration and determine the n value and k value; ② Where: Q ∞ ——The maximum adsorption molar amount of the solvent absorbed by the sample at swelling equilibrium; k is the adsorption constant, which indicates the strength of the interaction between the polymer and the solvent. The larger the k value, the greater the interaction between the polymer and the solvent. n——represents the mode of adsorption mechanism. The larger the n value, the faster the time to reach swelling equilibrium absorption.
[0011] Among them, the k value depends on the structural characteristics and the polymer-solvent interaction, that is, the interaction between the sample and the solvent.
[0012] f, calculate the diffusion coefficient In the curve graph, take the curve graph of 50% of the maximum adsorption molar amount, calculate the slope θ, and calculate the diffusion coefficient D according to formula ③. The diffusion coefficient D represents the rate at which the diffusion process occurs, and D is a kinetic parameter related to the activity of the polymer chain segment; ③ Where: D——Diffusion coefficient, unit is m 2 / s; h——indicates the thickness of the sample, in m; θ——indicates The slope of the linear portion of the curve before 50% of the maximum adsorption molar amount.
[0013] g, calculate the protection time The anti-virus time t is calculated by formula ④; t= ④ Where: t——indicates the anti-virus time.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for testing the anti-toxic performance of barrier materials. The method can calculate the anti-toxic time of barrier protective materials through simple testing and weighing steps, thereby avoiding waste of materials and effectively protecting test personnel from using barrier materials beyond the protection time, thereby reducing injuries to the staff, significantly reducing the use of mustard gas agents, and improving the design capabilities of barrier materials such as rubber and plastic. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The swelling rate curves of different zinc oxide dosages in the embodiment are shown in FIG. 0 to 24 h.
[0016] Figure 2 The swelling rate curves of the embodiments are shown in Figure 1 at different zinc oxide dosages for 0.5 to 4 hours. DETAILED DESCRIPTION
[0017] The specific embodiments of the present invention are described in detail below.
[0018] A method for testing the anti-toxic performance of a barrier material, the specific steps are as follows: a. Sample weighing Chlorobutyl rubber was taken as the test sample, and the formula of chlorobutyl rubber with different zinc oxide contents was shown in Table 1;
[0019] Take samples with a thickness of 0.5 mm from the sample to be tested, record them as 1#~5#, weigh and record the mass M1 of the sample, and the weighing result should be accurate to 1 mg.
[0020] b. Swelling The sample piece is naturally placed in 50mL of 2-CEES solvent, which is contained in a brown wide-mouthed frosted glass bottle with a stopper. The sample piece is shaken to completely immerse in the solvent. After the sample piece is immersed, the bottle stopper is tightly covered and sealed. The sealed bottle is stored at 36℃±1℃ in a constant temperature box. Samples are taken at intervals until the sample piece reaches swelling equilibrium, specifically, samples are taken at 0.5h, 1h, 2h, 4h, 6h, 8h, 10h, and 24h, respectively, to allow it to fully reach swelling equilibrium.
[0021] c. Sampling and processing Use tweezers to pick up the sample from the brown wide-mouthed frosted glass bottle with a stopper and place it on a clean and dry filter paper. Quickly close the filter paper and wipe off the solvent on the surface of the sample. Immediately use tweezers to pick up the sample and transfer it to a weighing bottle with a mass of M0 that has been constant. Immediately cover the weighing bottle cap and weigh it within 30 seconds. The total mass of the weighing bottle and the sample is recorded as M2, accurate to 1 mg. After weighing, shake off or blow off the remaining organic solvent in the weighing bottle before weighing the next sample.
[0022] d, calculation of molar amount of absorption solvent Molar amount of solvent absorbed by the sample Q t Determine it through the following formula ① Qt= ×100% ① Where: Qt – the molar amount of solvent absorbed by the sample at a specific time t; (M2- M0) - M1 – the mass of solvent absorbed by the sample; M1——Quality of the sample.
[0023] Calculate the molar amount Q of solvent absorbed by samples 1#~5# at time tt See Table 2,
[0024] e, draw the curve to calculate the diffusion coefficient According to step d, the molar amount of solvent absorbed by the sample at different times is plotted. The curve is obtained and the fitting equation ② is obtained, wherein the dynamic swelling data can be used to analyze the mechanism of penetration and determine the n value and k value; ② Where: Q ∞ ——The maximum adsorption molar amount of the solvent absorbed by the sample at swelling equilibrium; k is the adsorption constant, which indicates the strength of the interaction between the polymer and the solvent. The larger the k value, the greater the interaction between the polymer and the solvent. n——represents the mode of adsorption mechanism. The larger the n value, the faster the time to reach swelling equilibrium absorption.
[0025] According to formula ②, the data in Table 2 were processed to calculate the percentage of solvent absorption at different times. See Table 3, Qt and The swelling curve in the 0h~24h period is shown in Figure 1 ;
[0026] According to the data analysis in Table 3, the Qt of the chlorinated butyl rubber sample is less than 50% of its equilibrium adsorption capacity. The linear part is in the 0.5h~4h segment, see Figure 2 The n value and k value of the rubber sample with different zinc oxide dosage can be obtained, and the calculation results are shown in Table 4.
[0027]
[0028] At the same time, according to the data in Table 2, the Qt and The slope value of the linear portion, i.e., θ.
[0029] f, calculate the diffusion coefficient In the curve graph, take the curve graph of 50% of the maximum adsorption molar amount, calculate the slope θ, and calculate the diffusion coefficient D according to formula ③. The diffusion coefficient D represents the rate at which the diffusion process occurs, and D is a kinetic parameter related to the activity of the polymer chain segment; ③ Where: D——Diffusion coefficient, unit is m 2 / s; h——indicates the thickness of the sample, in m; θ——indicates The slope of the linear portion of the curve before 50% of the maximum adsorption molar amount.
[0030] According to formula ③, the diffusion coefficient of rubber in different zinc oxide vulcanization systems can be obtained. The specific results are shown in Table 5;
[0031] g, calculate the protection time The anti-virus time t is calculated by formula ④; t= ④ Where: t——indicates the anti-virus time.
[0032] According to formula ④, the anti-toxic time of the barrier material with different zinc oxide dosages was calculated, and the barrier material was taken for anti-toxic performance test. The results are shown in Table 6:
[0033] Comparing the predicted anti-gas time and the measured anti-gas time in the present invention, the test data is smaller than the predicted data. The main reason is that there are partial defects in the test piece when the rubber material is vulcanized. The presence of defects will cause the actual anti-gas thickness to decrease. Therefore, the test value is smaller than the predicted data. According to the GJB 1155A-2004 standard, the mustard gas "liquid-gas" anti-gas time is required to be no less than 360 minutes. Therefore, the above data error will not affect the judgment of the result under the condition of meeting the design of protective materials. This method is effective and feasible.
[0034] The scope of protection claimed by the present invention is not limited to the above specific embodiments. For those skilled in the art, the present invention may have various deformations and changes. Any modifications, improvements and equivalent substitutions made within the concept and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for testing the anti-toxic performance of barrier materials, characterized in that: The following steps are involved: a. Sample weighing Take a sample with uniform thickness from the sample to be tested, weigh and record the mass M1 of the sample, and the weighing result should be accurate to 1 mg; b. Swelling Place the sample piece naturally in 50 mL of 2-CEES solvent, shake it to make it completely immersed in the solvent, seal it and store it at 36℃±1℃, and take samples at intervals until the sample piece reaches swelling equilibrium; c. Sampling and processing After gently wiping off the solvent adhering to the surface of the sample, weigh the mass of the sample (M2-M0) to an accuracy of 1 mg; d, calculation of molar amount of absorption solvent Molar amount of solvent absorbed by the sample Q t Determine it through the following formula ① Qt= ×100% ① Where: Qt – the molar amount of solvent absorbed by the sample at a specific time t; (M2- M0) - M1 – the mass of solvent absorbed by the sample; M1 - the quality of the sample; e, draw the curve to calculate the diffusion coefficient According to step d, the molar amount of solvent absorbed by the sample at different times is calculated and plotted. Curve, and get the fitting equation②, determine the n value and k value; ② Where: Q ∞ ——The maximum adsorption molar amount of the solvent absorbed by the sample at swelling equilibrium; k——indicates the strength of the interaction between the polymer and the solvent. The larger the k value, the greater the interaction between the polymer and the solvent. n——Indicates the mode of adsorption mechanism. The larger the n value, the faster the time to reach swelling equilibrium absorption; f, calculate the diffusion coefficient In the curve graph, take the 50% portion of the curve graph of the maximum adsorption molar amount, calculate the slope θ, and calculate the diffusion coefficient D according to formula ③. The diffusion coefficient D represents the rate at which the diffusion process occurs; ③ Where: D——Diffusion coefficient, unit is m 2 / s; h——indicates the thickness of the sample, in m; θ——indicates The slope value of the linear part before 50% of the maximum adsorption molar amount in the curve; g, calculate the protection time The anti-virus time t is calculated by formula ④: t= ④ Where: t——indicates the anti-virus time.
2. The method for testing the anti-toxicity performance of barrier materials according to claim 1, characterized in that: In step a, the sample to be tested is any one of plastic, rubber-plastic blended material, and rubber-combined material.
3. The method for testing the anti-toxicity performance of barrier materials according to claim 1, characterized in that: In step a, the sample has a size of 15 mm × 15 mm and a thickness of 0.5 mm to 2 mm.
4. The method for testing the anti-toxicity performance of barrier materials according to claim 1, characterized in that: In step b, the 2-CEES solvent is placed in a brown frosted glass bottle with a wide mouth and a stopper. After the sample is immersed, the bottle stopper is tightly closed and sealed, and the bottle is stored in a constant temperature box at 36°C±1°C; samples are taken at 0.5h, 1h, 2h, 4h, 6h, 8h, 10h, and 24h respectively to allow it to fully reach swelling equilibrium.
5. The method for testing the anti-toxicity performance of barrier materials according to claim 1, characterized in that: Step c specifically includes the following steps: using tweezers to pick up a sample from a brown wide-mouthed frosted glass bottle with a stopper and place it on a clean and dry filter paper, quickly closing the filter paper and wiping off the solvent on the surface of the sample, immediately using tweezers to pick up the sample and transfer it into a weighing bottle with a mass of M0 that has been constant weight, and immediately closing the weighing bottle cap, weighing within 30 seconds, and the total mass of the weighing bottle and the sample is recorded as M2, accurate to 1 mg. After weighing, the remaining organic solvent in the weighing bottle is shaken off or blown off before weighing the next sample.